Transferts migratoires, institutions sociales migrantes et territorialité morale transnationale - Thomas Lacroix (L'Espace Politique)
How do those who stayed behind exert their authority over emigrants (notably to make sure they keep on sending remittances) despite the distance? How does power circulate beyond borders? For the last twenty years, the concept of territory is at the core of the scholarship on migrants’ spatiality and mobility. However, this paper turns upside down the common problematique by addressing the migratory space as a vector of the exercise of transnational authority. The paper draws on a series of qualitative investigation among emigrants from the Moroccan Middle-Atlas and Kabylia in Algeria. After a literature review of the use of the notion of territory in migration studies, it shows how a transnational territoriality is built up through the creation of migrant social institutions (transnational families, migrant associations and ethnic businesses) that serve as a relay for power dissemination. The transnational network of these social institutions is the crucible for the reproduction of a moral geography maintaining emigrants in a stance of obligation towards those who stayed. This moral geography is imbued with deeply ambivalent representations: the place of departure is simultaneously perceived as a place unable to sustain the social mobility of actors and a moral centrality. Conversely, the place of destination spurs a certain fascination while being perceived as corrupted by foreign values. This ambivalent moral geography underpins the moral economy of the relationship between migrants and non-migrants: while migration triggers fascination and envy, migrants are accused of selfishness and moral dubiousness when they do not abide to their duty of emigrants, and, in particular, when they refrain from transferring money to the left-behind.  Finally, drawing on the example of development projects undertaken in villages of departure, the article examines the way the transnational territory becomes henceforth a real stake for the renegotiation of rights and duties between actors.